Kehidupan Keluarga Nelayan di Era Pandemi Covid-19 di Desa Palang Kecamatan Palang Kabupaten Tuban - Ningrum, Elya Wahyu (Jurnal PUBLIQUE, 2022)
The problem examined in this study is about how the lives of fishermen's families in Palang village, Palang sub-district, Tuban district during the covid-19 pandemic. The family life of fishermen is a community whose majority the majority of their livelihoods as nelyan, they fulfill their daily needs by sailing at sea every day. In addition, the fishermen's community has several aspects of life including social aspects, social aspects can be seen from the relationships they run during the pandemic. Economic aspects, from the economic aspect, the income they get during this pandemic has decreased dramatically. Cultural aspects, From the cultural aspect, it can be seen from the way they carry out the existing culture during the pandemic. And the religious aspect, during the pandemic the religion of the fishermen still occurs and is carried out. From this study using qualitative research methods, using data collection techniques of observation, interviews, and documentation. The theory used to analyze the Family Life of Fishermen in the Era of the Covid-19 Pandemic In Palang Village, Palang Subdistrict, Tuban Regency, is the Social Action Theory-Max Weber.